An organic polymer-grafted ionic liquid as a catalyst for the cycloaddition of CO2 to epoxides. (12th December 2016) - Xing, Dan; Lu, Bin; Wang, Hongxia; Zhao, Jingxiang; Cai, Qinghai
Abstract : Chemical fixation of CO2 to a cyclic carbonate catalyzed by benzyl chloride polymer-supported imidazolium ionic liquids. Abstract : A facile method for synthesizing benzyl chloride polymer (BCP) has been developed and BCP immobilized N -methylimidazolium chloride (BCP-IMCl) was prepared by grafting N -methylimidazole ionic liquid on the BCP surface. The compositions and structures of BCP and BCP-IMCl were determined by gel permeation chromatography (GCP), FT-IR, NMR, and elemental analysis. BCP-IMBr, produced via the substitution of Cl − by Br −, was demonstrated to be an efficient catalyst for a solvent-free cycloaddition of CO2 to propylene epoxide (PO) to form propylene carbonate (PC), exhibiting a TON of 88.6 mol/molIL and a 98.7% selectivity towards PC formation. The catalyst can be easily recovered and effectively reused without a significant loss in its activity and selectivity, which would lead to its potential application foreground for the environmentally friendly synthesis of PC.